2012
DOI: 10.1088/2041-8205/757/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

DECREASING SUNSPOT MAGNETIC FIELDS EXPLAIN UNIQUE 10.7 cm RADIO FLUX

Abstract: Infrared spectral observations of sunspots from 1998 to 2011 have shown that on average sunspots changed, the magnetic fields weakened, and the temperatures rose. The data also show that sunspots or dark pores can only form at the solar surface if the magnetic field strength exceeds about 1500 G. Sunspots appear at the solar surface with a variety of field strengths, and during the period from 1998 to 2002 a histogram of the sunspot magnetic fields shows a normal distribution with a mean of 2436 ± 26 G and a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 19 publications
9
112
9
Order By: Relevance
“…Watson et al (2011) Regardless of whether 2012 or 2013 is adopted as the maximum of cycle 24, we find a positive temporal gradient of the magnetic field strength with time in the rising phase of this cycle that is three times larger than the one-σ error margin. This is inconsistent with Livingston et al (2012), who claimed a monotonic decrease of the sunspot field strength through the whole cycle.…”
Section: Temporal Variation Of the Umbral Field Strengthcontrasting
confidence: 73%
See 3 more Smart Citations
“…Watson et al (2011) Regardless of whether 2012 or 2013 is adopted as the maximum of cycle 24, we find a positive temporal gradient of the magnetic field strength with time in the rising phase of this cycle that is three times larger than the one-σ error margin. This is inconsistent with Livingston et al (2012), who claimed a monotonic decrease of the sunspot field strength through the whole cycle.…”
Section: Temporal Variation Of the Umbral Field Strengthcontrasting
confidence: 73%
“…We used a Kolmogorov-Smirnov test (Press et al 1992) to measure the distance of the sample of the magnetic field strengths of sunspots against a given distribution to determine the best distribution for each cycle. The distribution of the umbral field strength is well represented by a Gaussian (same as, e.g., Livingston et al 2012). The widths of our distributions (Gaussian width =375 and 364 ± 20 G for cycles 23 and 24) are close to the 320 G reported by Livingston et al (2012).…”
Section: Long-term Variation Of the Umbral Field Strength And Intensitysupporting
confidence: 73%
See 2 more Smart Citations
“…It is traced with several quantities, including the number and area of sunspots (Hoyt & Schatten 1996;Hathaway et al 2002;Usoskin 2008;Hathaway 2010). The cyclic variation of umbral properties such as intensity and magnetic field strength was subject of several investigations (Livingston 2002;Penn & Livingston 2006;Penn & MacDonald 2007;Penn & Livingston 2011;Livingston et al 2012;Pevtsov et al 2013). Among others, Albregtsen & Maltby (1978) and Albregtsen et al (1984) found that the umbral intensity fluctuates in phase with the solar cycle such that the umbrae are brighter at the end of a cycle.…”
Section: Introductionmentioning
confidence: 99%